Evaluación de los factores de riesgos ergonómicos en el área de producción de la empresa “La Pepa de Oro Tropical Tropicalgold S.A”, y su incidencia en la salud ocupacional de los trabajadores. Propuesta de un manual de prevención. - Zambrano, José (2018)
The main objective of this study is evaluating the ergonomic risk factors in the production area of the company LA PEPA DE ORO TROPICAL TROPICALGOLD SA, the process begins with the diagnosis situation of the company regarding personnel, work process, occupational accident and industrial safety management, then the identification of occupational hazards present in the workplace was realized and focused on the ergonomic risks where objective assessment goes along with the participation of the staff through a subjective assessment, then we measured and evaluated the Risks by means of the NTP 330 Methods for Risk Factors and Ergonomic Methods REBA which determined that 80% of the operations require immediate actions and the JSI Method determined that 43.34% of operations require preventive and corrective actions to avoid disturbances or injuries. The application of these studies allowed to carry out an Ergonomics Preventive Management Program which cost or benefit ratio is 2.06, that is to say for each dollar invested in prevention represents a benefit of $ 2.06, this program is supported by the development of an Ergonomic Risk Prevention Manual which will allow the dissemination of preventive rules for all the personnel.